Effectiveness of a Nursing-Based Fast Track Surgery Protocol on Postoperative Pain Reduction: A Quasi-Experimental Study - Ariani, Sri Purwanti; Yuhansyah, Yuhansyah; Ernawati, Ernawati; Jariyah, Ainun (Journal of Applied Nursing and Health, 2025)
Background: Ineffective management of postoperative pain can delay recovery, increase the risk of complications, and extend the length of hospital stay. Fast Track Surgery (FTS) is a multidisciplinary approach that speeds up recovery and reduces postoperative pain effectively. However, studies on the effectiveness of nursing-based FTS interventions in regional hospitals are still limited. This study examines the effectiveness of an innovative nursing-based FTS approach in reducing pain intensity among postoperative patients. Methods: This quasi-experimental study used purposive sampling and involved 30 participants, divided into intervention and control groups. The study was conducted at TK III Dr. R. Soeharsono Hospital in Banjarmasin, South Kalimantan. Inclusion criteria were patients aged 18 to 65 years, postoperative, able to communicate well, and willing to participate. Pain intensity was measured using the Visual Analog Scale (VAS) before and two hours after the Fast Track Surgery intervention. The nursing-based FTS intervention included preoperative education, early mobilization, and multimodal analgesia management. The study was reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines to ensure clarity and completeness. Results: Most participants were between 19 and 44 years old, 60% were male, and the majority had completed high school. Before the intervention, patients mainly reported moderate to severe pain; after the FTS intervention, most reported mild pain. Pain intensity was significantly different between the intervention and control groups (p < 0.001). Conclusion: The nursing-based Fast Track Surgery approach effectively reduces postoperative pain intensity. It is recommended that nurse-led FTS protocols be implemented in regional hospitals to improve pain management and accelerate patient recovery.